Where is the Princess? - Oyelese, Olufunmilayo (Heinemann Educational Books Ltd, 1980)
Where is the princess?What has happened to her?Nobody seems to have a clue.The princess has just disappeared.But How?When?
Keywords: Adventure; Disappearance; Juvenile Fiction